2001
DOI: 10.1292/jvms.63.1331
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus and Syringomyelia in a Cat.

Abstract: ABSTRACT. A 3-month-old male Japanese cat with feline parvovirus infection, showing central and cervical nerve abnormalities, was diagnosed as hydrocephalus and syringomyelia by use of magnetic resonance imaging (MRI). The cat was maintained clinically by medical treatment even though he could not stand. The MRI scans obtained about 5 months later showed that the ventricles had increased in size and the cervical syrinx had extended into the thoracic spinal cord. Ventriculoperitoneal (VP) shunt was performed. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…In cats, dilation of the cerebral ventricular system is frequently secondary to viral infection (Tani et al 2001;Benigni and Lamb 2005;Hori et al 2015;Keating et al 2016). In utero infection with parvovirus can cause cerebellar hypoplasia which affects the external germinal layer of the cerebellum and prevents the formation of the granular layer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In cats, dilation of the cerebral ventricular system is frequently secondary to viral infection (Tani et al 2001;Benigni and Lamb 2005;Hori et al 2015;Keating et al 2016). In utero infection with parvovirus can cause cerebellar hypoplasia which affects the external germinal layer of the cerebellum and prevents the formation of the granular layer.…”
Section: Discussionmentioning
confidence: 99%
“…In utero infection with parvovirus can cause cerebellar hypoplasia which affects the external germinal layer of the cerebellum and prevents the formation of the granular layer. Hydrocephalus and hydranencephaly have been found to occur concurrently with parvovirus infection (Tani et al 2001;Keating et al 2016). Taga et al (2000) reported acquired hydrocephalus and hydromyelia in a cat with FIP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations